2017
DOI: 10.1080/20964129.2017.1335933
|View full text |Cite
|
Sign up to set email alerts
|

Simulating land-use change and its effect on biodiversity conservation in a watershed in northwest China

Abstract: Introduction: Land-use management strategies play a major role in biodiversity change. In many parts of the world, local governments are under increasing pressure to regulate human activity to mitigate negative impacts on ecosystems. Outcomes/other: This study aimed to analyze the effects of different land-use patterns on biodiversity change across a typical artificial desert watershed. We first analyzed land-cover change based on past and future management scenarios in a watershed spanning Gaotai, Linze, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…The investigators used the InVEST Habitat Quality model and demonstrated spatial approaches to classifying landscapes for habitat quality based on the size, density, and distribution of native vegetation in the landscape. A study in China modeled land use change and its effect on biodiversity conservation using two land use management scenarios [42]. The investigators developed scenarios based on the protection levels of the local government plans and projected biodiversity at local and regional scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators used the InVEST Habitat Quality model and demonstrated spatial approaches to classifying landscapes for habitat quality based on the size, density, and distribution of native vegetation in the landscape. A study in China modeled land use change and its effect on biodiversity conservation using two land use management scenarios [42]. The investigators developed scenarios based on the protection levels of the local government plans and projected biodiversity at local and regional scales.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum distance, habitat suitability, relative sensitivity of habitats to threats (higher numbers indicate more habitat suitability and more sensitivity to threats). Source: [38][39][40][41][42][43][44].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…where R is the number of all the ecological threat factors, D xj is the set of all grid cells on raster map r, W r is the threat weight that relates the destructiveness of a degradation source to all habitats, r y indexes all grid cells in raster map r, i rxy is a function describing the exponential decay in habitat quality as a function of distance from ecological threat factors, β x is the level of accessibility to grid cell x, with 1 indicating complete accessibility and 0 complete inaccessibility, and S jr is the sensitivity of land use type j (habitat type) to the ecological threat factor r. Finally, the habitat quality Q xj of LULC j is calculated based on the habitat suitability of LULC j using [48,62]:…”
Section: Modelling Habitat Quality Using the Invest Modelmentioning
confidence: 99%
“…Xu et al (2013) identified and calculated the biodiversity hotspots by InVEST biodiversity model in the Wenchuan earthquake-hit area. Liang and Liu (2017) analyzed the effects of different land-use patterns on biodiversity change based on InVEST biodiversity model and simulation method in Zhangye, China. In summary, integration of InVEST model, satellite image and landscape ecological methods to assess the regional biodiversity was feasible (Lausch et al, 2016;Remme et al, 2016;Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%